Is Regioselectivity in the Enzyme‐Catalyzed Hydroperoxidation of Arachidonic Acid Necessarily Determined by Hydrogen Abstraction? The Case of Rabbit Leu597Ala/Ile663Ala ALOX15 Mutant. Issue 20 (19th August 2016) - Saura, Patricia; Masgrau, Laura; Heydeck, Dagmar; Kühn, Hartmut; Lluch, José M.; González‐Lafont, Àngels
Abstract: Molecular dynamics simulations and quantum mechanics/molecular mechanics calculations were performed on the in silico Leu597Ala/Ile663Ala double mutant of rabbit ALOX15 (12/15 lipoxygenase). The computational results suggested that subtle steric hindrance by the conserved Leu597 and C‐terminal Ile663 residues disturbed H10 abstractions in wildtype ALOX15 (which abstracts H13), but if these two bulky residues were mutated to smaller ones, H10 abstraction was no longer impeded and the regioselectivity of the initial H‐abstraction step was changed. However, site‐directed mutagenesis with HPLC analysis of the products of the whole oxidation process showed that the regioselectivity of the hydroperoxidation was not altered. This disagreement may be explained by the conformational reorganization of the system needed to rotate the −OO . group from an antarafacial to a suprafacial arrangement prior to back‐hydrogen transfer. After H10 abstraction and O2 insertion, the evolution of the peroxy radical at C12 was sterically impeded, whereas peroxyl group rotation at C15 (after H13 abstraction) could easily evolve to a suprafacial arrangement, which thus led to the final product. For this reason, the global regiospecificity was not affected in the mutant. These findings exemplify that the regioselectivity of initial hydrogen abstraction and the regioselectivity of the final product do not necessarily coincide (in fact, they can be opposite) for the hydroperoxidation of arachidonic acid catalyzed by a lipoxygenase. Abstract : Going abstract : A suitable mutation introduced in the enzyme ALOX15 (15‐lipoxygenase‐1) can change the regio‐selectivity of initial hydrogen abstraction, but the regioselectivity of the final arachidonic acid hydroperoxide product remains invariant.